2010
DOI: 10.1155/2010/863985
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Influenza by Cytotoxic T-Cells: Calling for Help from Destroyers

Abstract: Influenza is a vaccine preventable disease that causes severe illness and excess mortality in humans. Licensed influenza vaccines induce humoral immunity and protect against strains that antigenically match the major antigenic components of the vaccine, but much less against antigenically diverse influenza strains. A vaccine that protects against different influenza viruses belonging to the same subtype or even against viruses belonging to more than one subtype would be a major advance in our battle against in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 129 publications
0
10
0
1
Order By: Relevance
“…This might be of particular interest, since it was shown that CD4 + and CD8 + T-cell responses to influenza could partially confer protection from heterologous IAV infection [28][31]. It is further known that CTL responses play an important role in controlling RSV infection [32]–[34].…”
Section: Discussionmentioning
confidence: 99%
“…This might be of particular interest, since it was shown that CD4 + and CD8 + T-cell responses to influenza could partially confer protection from heterologous IAV infection [28][31]. It is further known that CTL responses play an important role in controlling RSV infection [32]–[34].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-protective adaptive immunity is important in antigenically dissimilar influenza viruses, as has been shown in animal studies and limited human studies (8,9,17,(38)(39)(40)(41)(42)(43). There is strong evidence in the literature that CD8+ T cells play a large role in providing such cross-immunity to influenza virus that has drifted enough to evade neutralizing antibodies (13,14,17,38,(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…One strategy to induce heterosubtypic immunity is vaccination with a formulation that has the capacity to induce cross-reactive CD8+ cytotoxic T lymphocyte (CTL) responses against conserved antigens shared by different influenza virus subtypes [5] , [7] , [8] . CTL-mediated heterosubtypic immunity, although unable to neutralize the virus and prevent infection, could facilitate clearance of the virus, thereby controlling the course of infection [5] , [9] .…”
Section: Introductionmentioning
confidence: 99%